Understanding variation in the design of China's new co-operative medical system - Brown, Philip H.; de Brauw, Alan; Du, Yang (Cambridge University Press, 2009)
Although the New Co-operative Medical System (NCMS) was expected to operate in all rural Chinese counties by the end of 2008, county governments were given significant leeway in the design of the local programmes. As a result, fundamental characteristics of NCMS programmes vary dramatically between counties. Such heterogeneity in programme design may influence satisfaction with the NCMS in each county, and thus each programme's prospects for success. This article uses survey data collected by the authors to consider five distinct measures of success. We find that households respond favourably to making emigrants eligible for coverage and to lowering the spending threshold for reimbursement eligibility. However, households are less likely to have received reimbursement in counties that require referrals or limit treatment to approved hospitals. Finally, out-of-pocket expenditures associated with catastrophic health care may still be too high to facilitate treatment of the rural poor.